Implications of Tumor Location on Subtypes of Medulloblastoma. Issue 9 (19th March 2013) - Teo, Wan‐Yee; Shen, Jianhe; Su, Jack Meng Fen; Yu, Alexander; Wang, Jian; Chow, Wing‐Yuk; Li, Xiaonan; Jones, Jeremy; Dauser, Robert; Whitehead, William; Adesina, Adekunle M.; Chintagumpala, Murali; et al.
Abstract Background Medulloblastoma (MB) comprises of four molecular subtypes, Sonic hedgehog (SHH), Wingless (WNT), Groups 3 and 4. WNT‐subtype MBs were found to arise from midline of the brainstem occupying the fourth ventricle while SHH‐subtype occupied the cerebellar hemisphere in a small subset of patients. Procedure We tested this hypothesis in a large cohort of pediatric MBs comprising of all four molecular subtypes. Results We validated in the first comprehensive analysis of tumor location of 60 human MBs representative of the four molecular subtypes, that hemispheric tumors are significantly associated with SHH‐subtype MBs while midline tumors with WNT‐subtype, Group 3 and 4 MBs (P < 0.001). Nearly half of SHH‐subtype MBs were midline. Conclusions Tumor location should not be generalized to MB subtypes. SHH‐subtype MBs are not exclusively hemispheric and hemispheric MBs are not always SHH‐activated. It is imperative to identify subtypes in conjunction with tumor location when exploring currently available targeted therapy. Pediatr Blood Cancer 2013;60:1408–1410. © 2013 Wiley Periodicals, Inc.